A comparative analysis of pregnancy outcomes of patients with uterine fibroids after high intensity focused ultrasound ablation and laparoscopic myomectomy: a retrospective study. (1st January 2021) - Jiang, Zhaoying; Li, Qing; Li, Waixing; Zhu, Xiaogang; Jiang, Jianfa; Chen, Lixing; He, Sili; Xue, Min; Ye, Mingzhu; Li, Xilei
Abstract: Purpose: The aim of this study was to retrospectively compare and analyze pregnancy outcomes of patients with uterine fibroids after high intensity focused ultrasound (HIFU) ablation and laparoscopic myomectomy (LM). Materials and methods: The study group consisted of 346 patients with uterine fibroids who wished to conceive, in which 152 patients received HIFU ablation treatment (HIFU group) and 194 patients received LM treatment (LM group). The parents' baseline characters were recorded and the pregnancy outcomes were evaluated in a median follow-up time of 42 months (range: 16 ∼ 81) after the treatment, and the differences of the two groups were compared. Results: Patients with uterine fibroids in HIFU group had a significant shorter pregnancy interval than that in LM group (10 months VS. 13 months, p  < .05). No significant differences were observed in pregnancy rate, miscarriage rate, live birth rate, natural pregnancy rate, cesarean section rate, and perinatal complications rate between the HIFU group and the LM group ( p  > .05). When stratified by age, infertility history, fibroid types, fibroid numbers, and fibroid sizes, there was no statistically significant difference in pregnancy rate between the HIFU group and the LM group ( p  > .05). Conclusions: Based on the results from this study, both HIFU and LM can be safely used to treat patients who wish to conceive. The pregnancy outcomes of post-HIFU are similar to that of post-LM.